Integrating IoT in Healthcare Systems: A Socio-Technical Approach to Improving Healthcare Delivery in Afghanistan - Jawad Danish; Abdul Wahid Samadzai; Hakimi, Musawer; Mohammad Aziz Rastagari (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
The integration with the Internet of Things (IoT) technology with health systems shows a strong potential to re¬invent at least the developed areas of Afghanistan. The study is focused on the perceptions, challenges and willingness of the stakeholders to identify the potential benefits, barriers and strategies to implement IoT-based Health monitoring systems. So, this study uses a mixed-method research approach. A cross-sectional web-based survey was conducted, with 150 possible participants (stakeholders), including healthcare professionals and computer scientists. The survey confirmed acquainting individuals with IoT, their perceived benefits of IoT, possible challenges and willingness of the participants to adopt IoT in the context mentioned above. Main data analyses included descriptive statistics, crosstabs and regression analysis results using the SPSS data processing software. The findings demonstrated that 73.33% of the respondents assumed IoT to improve health monitoring and about 80% showed willingness to adopt IoT. According to this study, the major challenges mentioned by respondents are lack of infrastructure, data security issues, and costs involved. It was identified that In the regression analysis (R²=0.82), benefit, familiarity, and awareness of IoT technology positively influenced willingness to adopt. Integration was supported by younger and better-educated people. As a result, we will consider gap closing the infrastructure, strengthening data security and raising awareness through direct educational campaigns as a priority area for ensuring the success of IoT adoption. The results of the study highlight aspects which may come handy for the policymakers and health care practitioners to facilitate its adoption in a cost-effective and culture-sensitive manner to address the health particularities of the developing nations.